A response to Steubing et al., "Effects of systematic phonics instruction are practically significant": The origins of the National Reading Panel. - Camilli, Gregory; Kim, Sun Hee; Vargas, Sadako (Education Policy Analysis Archives, 2008)
A recent article by Stuebing, Barth, Cirino, Francis and Fletcher critiqued the findings of Camilli, Vargas, and Yurecko (2003) and Camilli, Wolfe, and Smith (2006). With a methodological argument, they attempted to resolve the conflict between these studies and the original report Teaching Children to Read (National Reading Panel, 2000). In response, it is argued that three issues must be considered in a fair assessment of the NRP report—program labels or bins, alternative bins, and the role of literacy activities in reading instruction. In this light, three hypotheses ventured by Stuebing etal. are analyzed. It is concluded that the argument by Stuebing et al. does not reveal flaws in the original NRP report by Camilli et al. (2003), though some points of agreement are acknowledged.